ANALISIS USAHATANI KELAPA-DALAM (Cocos nucifera L.) BERDASARKAN AKSESIBILITAS WILAYAH DI PROVINSI JAMBI - Rozaina Ningsih; Fachrurrozi Sjarkowi; Marwan Sufri; Dessy Adriani (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2018)
This study aims at analyzing the farming of the magnitude of cost, revenue, earnings and the level of farm efficiency of coconut (Cocos nucifera L) based on the accessibility of the plantation area.. The research site was done purposively in two districts, namely Tanjung Jabung Barat and Tanjung Jabung regency in Jambi province with a consideration that those area are the center of coconut farming. Results of the farming analysis showed that: the average of total cost was 6,895,159 rupiahs / ha / year, the average of reception was Rp.25.993.293/ ha / year and the average of income was 19,098,135 rupiahs / ha / year in general, the value of R / C ratio was 3.74 which meant there would be a chance to be developed as it was efficiently valuable. Dealing with the access to the plantation (1) For non-isolated area (D = 1): the cost average was 6,489,809 rupiahs / ha / year, the reception average was Rp.29.728.646 / Ha / year and revenue average was Rp.23.238.837 / ha / year, the value of R / C ratio was 4.58 which meant there would be a chance to be developed as it was efficiently valuable, (2) For isolated areas (D = 0): the cost average was 7,411,059 rupiahs / ha / year, the reception average was 21,239,209 rupiahs / ha / year, and the income average was 13,828,149 rupiahs / ha / year, the value of R / C ratio was 2.87 average, but the value of R / C ratio for the isolated region is smaller than the non-isolated.